FETAL WEIGHT ESTIMATION USING FRACTIONAL FETAL THIGH VOLUME - Nikolovski, Sotir; Matik, Stefan; Dimitrovska, Gordana Ristevska; Nikolova, Dafina; Trpchevska, Emilija Nikolovska; Janevska, Vesna (Journal of Morphological Sciences, 2020)
Introduction: Three-dimensional ultrasound as a new method for fetal weight estimation makes it possible to calculate fetal weight by obtaining volumes of different parts of the fetus such as fetal thigh volume (VolTh), which is quickly measured and highly reproducible between different observers. Aim: The aim of this study is to determine the accuracy of calculating the fetal weight based on thigh volume (VolTh) obtained by three-dimensional ultrasound in relation to the actual birth weight. Methods: A cross-sectional study in which 120 pregnant women who gave birth were included. Each patient`s anamnesis with an emphasis on inclusion and exclusion criteria was taken. Then, using a three-dimensional ultrasound, the volume of the fetal thigh (VolTh) was recorded, and after birth the actual birth weight of the neonate was measured. Results: 116 patients met the inclusion criteria. The simple linear regression analysis revealed a regression equation of birth weight as: Estimated fetal weight = 24.233 x fractional volume of the thigh + 1513.8 , with a coefficient of determination R 2 =0.5761. To evaluate the precision of the new linear regression formula in birthweight prediction, a comparison among the new formula and other formulas was conducted, including Lee`s formula, Schild`s formula, Srisantiroj`s formula and the new formula. The mean absolute percentage errors (MAPE) were 8.6%, 42.41%, 8.14% and 7.2%, respectively. Conclusion: The study showed that fetal weight can be estimated using 3D ultrasound techniques including fractional volumetry of the fetal thigh. Key words: 3-dimensional ultrasound (3DUS); Birth weight (BW); Thigh volume (VolTh)